2023
DOI: 10.4103/indianjpsychiatry.indianjpsychiatry_306_22
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem and social media addiction level in adolescents: The mediating role of body image

Abstract: Background: There are many studies examining the relationship between social media and self-esteem. Studies examining the relationships between the self-esteem, social media use, and body image of adolescents are limited in the literature. Aim: This study aimed to examine the relationship between self-esteem and social media addiction levels in adolescents and the mediating role of body image in the relationship between these two variables. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…We found that the level of education was not significantly associated with self-esteem among social media users. Our finding was consistent with the finding of Colak et al [ 13 ]. On the other hand, Özcan et al [ 25 ] showed that there was a significant relationship between education levels and the self-esteem levels of adolescents, and as the education levels increase, self-esteem levels also increase.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…We found that the level of education was not significantly associated with self-esteem among social media users. Our finding was consistent with the finding of Colak et al [ 13 ]. On the other hand, Özcan et al [ 25 ] showed that there was a significant relationship between education levels and the self-esteem levels of adolescents, and as the education levels increase, self-esteem levels also increase.…”
Section: Discussionsupporting
confidence: 94%
“…Many studies assessed the effect of social media on self-perception of body image. Colak et al [ 13 ] examined the relationship between self-esteem, social media addiction, and body image in high school students. There was a negative moderate relationship between self-esteem and social media addiction levels and a positive correlation between self-esteem and body image.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could therefore lead to the development of eating disorders if not addressed on time. Our literature search found that abnormal eating behaviours were predominantly studied in children[ 2 ] and adolescents,[ 2 3 4 ] with limited studies done in the young adult population, university and college students with studies reporting 31% to 42% prevalence of abnormal eating behaviours. [ 5 6 7 ]…”
mentioning
confidence: 99%